Enhancing polyvinyl alcohol (PVA) nanocomposites: key properties, applications and challenges in advanced engineering - Jailani, Azrol; Hidzer, M. Hazim; Firdaus, A. H.M.; Sapuan, S. M.; Zainudin, Edi Syams; Atiqah, Afdzaluddin; Wan Jaafar, Wan Munira; Suryanegara, Lisman (KeAi Communications, 2026)
This review highlights the performance enhancement of polyvinyl alcohol (PVA) composites through the incorporation of nanofillers, focusing on mechanical, thermal, electrical and piezoelectric improvements. It examines bio-based fillers such as nanocellulose cellulose nanofibrils (CNF) and cellulose nanocrystals (CNC), and carbon-based fillers like graphene nanoplatelets (GNP) and carbon nanotubes (CNT). CNF and CNC increase tensile strength by up to 40% and 17.9%, respectively, due to their ability to reinforce polymer networks. CNC also improves thermal stability, raising degradation temperatures to approximately 327 °C through enhanced hydrogen bonding. Electrical and piezoelectric properties are significantly improved, with dielectric behaviour enhanced by up to 107% and open-circuit voltage reaching 25.6 V, suitable for energy harvesting. GNP and CNT contribute by forming conductive networks within the PVA matrix, enabling superior electrical conductivity and consistent piezoresistive responses under strain. These characteristics make such composites ideal for applications in flexible electronics, sensors, structural health monitoring and other advanced fields. This synthesis of experimental results and critical insights underscores the broad utility and future potential of nanofiller-enhanced PVA composites across aerospace, automotive, healthcare, and defence sectors.